Effects of sublethal concentrations of zinc nanoparticles on bioaccumulation and cellular response in the Rabbitfish Siganus rivulatus - Mohamed E.A. El-Metwally; Arafah M. Emam; Mahmoud M. Maaty; Nahla HE. M. Ahmed (Egyptian Journal of Aquatic Research, 2023)
Zinc oxide nanoparticles (ZnONP) are increasingly utilized in many products worldwide. Eventual release into the aquatic system poses various environmental hazards and raises concerns for aquatic life and public health. In the present study, the effects of waterborne ZnONP and dissolved Zn+2 (ZnSO4 7H2O) were investigated in Siganus rivulatus through experimental exposure to environmentally relevant concentrations (40, 200, and 400 µg/L) of Zn in both forms. Fish exposed to ZnONP exhibited a higher accumulation of zinc in their muscles, whereas exposure to Zn+2 ions led to elevated zinc levels in the gills and liver. The physiological and histopathological analyses revealed distinct responses between the two experimental groups. ZnONP exposure stimulated the antioxidant system, resulting in a significant elevation (1.7–2 folds) of superoxide dismutase (SOD) and catalase (CAT) enzymes in the gills. On the other hand, Zn+2 ions increased the levels of SOD, CAT, and Glutathione-S-transferase (GST) enzymes 1.5–2.4 times in the liver, along with 1.9–2 folds higher lipid peroxidation (LPO) in both the liver and gills. Histological examination of the gills revealed lamellar fusions, degenerative alterations, and infiltration of melanomacrophagic centers, indicating the impact of both treatments. Similarly, the liver tissue showed cytoplasmic vacuolation and significant infiltration of melanomacrophagic centers engorged with brown spots. These histopathological changes were more severe in fish exposed to all concentrations of Zn+2 and in fish exposed to 400 µg/L of ZnONP. This study concludes that waterborne Zn+2 exhibited higher toxicity in fish liver and gills compared to ZnONP. However, the mechanisms of ZnONP uptake by fish tissues remain unclear and require further investigation.